Redwall - Jacques, Brian; Chalk, Gary (New York : Berkley, 1986)
When the peaceful life of ancient Redwall Abbey is shattered by the arrival of the evil rat Cluny and his villainous hordes, Matthias, a young mouse, determines to find the legendary sword of Martin the Warrior which, he is convinced, will help Redwall's inhabitants destroy the enemy.
A tale of Redwall.
Keywords: Mice -- Fiction; Animals -- Fiction; Fantasy